Four new species of the genus Thoracophorus Motschulsky, 1857 for the Neotropical region (Coleoptera: Staphylinidae: Osoriinae) - Irmler, Ulrich (Zootaxa, 2015)
Four new species of the genus Thoracophorus Motschulsky, 1857 of the Neotropical region are described: T. verhaaghi n. sp., T. zicsii n. sp., T. struyvei n. sp., and T. perplexus n. sp. The new species originate from French Guiana, Peru, and Ecuador. Similar species T. filum Sharp, 1887, T. proximus Irmler, 1985, T. exilis (Erichson, 1840) and T. aequalis Sharp, 1887 are compared to discuss differences between them and the newly described species and their known distribution.